2016
DOI: 10.1007/s12035-016-0085-y
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Attenuates Aβ Pathology Mediated Through Levamisole Sensitive Nicotinic Acetylcholine Receptors in a C. elegans Model of Alzheimer’s Disease

Abstract: The metabolic disease, type 2 diabetes mellitus (T2DM), is a major risk factor for Alzheimer's disease (AD). This suggests that drugs such as metformin that are used to treat T2DM may also be therapeutic toward AD and indicates an interaction between AD and energy metabolism. In this study, we have investigated the effects of metformin and another T2DM drug, 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) in C. elegans expressing human Aβ. We found that Aβ expressed in muscle inhibited levamisole sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 86 publications
2
17
0
Order By: Relevance
“…These remarkable results point out the possible mode of action of CLE metabolites apart from conventional criteria, such as interactions with Aβ-related proteins like the peroxisome proliferator-activated receptor gamma (PPARγ) and pro-apoptotic proteins—respectively known to be upregulated and downregulated by natural products such as epigallocatechin gallate (EGCG) in green tea [29]. Further, CLE may instead be interacting with known proteins affecting Aβ deposition in C. elegans , such as DAF-2 and FOXO [46,47], all of which warrant further investigation on the possible mechanisms on CLE metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…These remarkable results point out the possible mode of action of CLE metabolites apart from conventional criteria, such as interactions with Aβ-related proteins like the peroxisome proliferator-activated receptor gamma (PPARγ) and pro-apoptotic proteins—respectively known to be upregulated and downregulated by natural products such as epigallocatechin gallate (EGCG) in green tea [29]. Further, CLE may instead be interacting with known proteins affecting Aβ deposition in C. elegans , such as DAF-2 and FOXO [46,47], all of which warrant further investigation on the possible mechanisms on CLE metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…As MICA restored cholinergic neurotransmission in worms that express Aβ in muscle cells, we reasoned that MICA might also reduce Aβ-mediated toxicity in worms that express Aβ in neurons. In our previous study, we found that metformin, a well-known hypoglycemic agent, improved chemotaxis and restored normal serotonin-sensitivity in worms that express Aβ in neurons [2]. Similar findings were observed for MICA in this study suggesting that the two compounds have a similar mode of action.…”
Section: Discussionsupporting
confidence: 88%
“…As we found negative effects of glucose enrichment on AD progression, we hypothesized that the antidiabetic drugs' metformin and AICAR could also be beneficial in AD. Both metformin and AICAR reduced Aβ -mediated toxicity in worms suggesting that anti-diabetic drugs might be helpful to slow/ overcome AD pathogenesis [608].…”
Section: Chapter # Viii: General Discussionmentioning
confidence: 99%
“…For instance, we have previously shown that antioxidant treatment, using the mitochondrial-targeted antioxidant MitoQ, was able to ameliorate depletion of the mitochondrial lipid cardiolipin and improved the healthspan of another strain of transgenic AD nematodes with muscular expression of Aβ (CL2006) 35 . Treatment using an antidiabetic drug, Metformin, has also recently been shown to delay Aβ-related paralysis, and improve neuronal transmission, in two transgenic AD strains, one with inducible muscular (CL4176) and one with neuronal Aβ expression (CL2355) 36 . However, the mechanisms underlying the beneficial AD effects of such metabolism-related drugs are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%